The Relationship between Self-Efficacy and Burnout of Implementing Nurses in the Implementation of Discharge Planning - Sari, Ni Luh Putu Mira Santana; Yuniarti, Lucia Ni Luh; Sudiarta, I Ketut (Journal of Language and Health, 2024)
Self-efficacy implementing nurse is a belief and ability of a nurse in implementing discharge planning that aims to improve the quality of health that will affect the continuity of ongoing care for patients. The purpose of this study was to identify the determinant factors of self-efficacy of implementing nurses and analyze the most dominant factors in the implementation of discharge planning. The design used in this study was cross-sectional with a sample of 187 implementing nurses selected through simple random sampling using a questionnaire as an instrument. Data were analyzed univariately, bivariately with the chi square test, and multivariately with the binary logistic regression test. The results of the bivariate analysis of the burnout variable (p 0.002) had a significant relationship in the implementation of discharge planning. It is expected that implementing nurses can increase their self-efficacy values through improving good self-function so that it has an impact on the quality of service in the implementation of discharge planning.